2016
DOI: 10.1021/acs.jproteome.6b00006
|View full text |Cite
|
Sign up to set email alerts
|

The Peripheral Blood Eosinophil Proteome

Abstract: A system-wide understanding of biological processes requires a comprehensive knowledge of the proteins in the biological system. The eosinophil is a type of granulocytic leukocyte specified early in hematopoietic differentiation that participates in barrier defense, innate immunity, and allergic disease. The proteome of the eosinophil is largely unannotated with under 500 proteins identified. We now report a map of the nonstimulated peripheral blood eosinophil proteome assembled using two-dimensional liquid ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
112
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(120 citation statements)
references
References 49 publications
(128 reference statements)
7
112
1
Order By: Relevance
“…According to our previous (15) and current study, proteomic analyses of EOS demonstrated a low level of individual variation with the exception of HLA proteins with coefficients of variation >1. Therefore, despite the limited number of EOS donors included in this study, we believe our data set to be highly representative of the general allergic population with rhinitis with or without mild asthma.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…According to our previous (15) and current study, proteomic analyses of EOS demonstrated a low level of individual variation with the exception of HLA proteins with coefficients of variation >1. Therefore, despite the limited number of EOS donors included in this study, we believe our data set to be highly representative of the general allergic population with rhinitis with or without mild asthma.…”
Section: Resultssupporting
confidence: 76%
“… IBAQ values from Wilkerson et al 15 were compared with the fold change (FC) log2 ratios of the intensities of reporter ions from IL-3 treated (I) and vehicle control (V) EOS, the log2 ratios expressed as of % vehicle control, and q-values for differences between the treated and control EOS. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…ImageJ immuno-blot quantification of the relative band intensities for MYDGF in eosinophil lysates compared to 10 ng of recombinant protein ( Figure 1B) indicated that ~2 ng MYDGF is present in the lysate of 2x10 5 eosinophils. This figure is within 10-fold of 17 ng MYDGF per 2x10 5 eosinophils that can be estimated by relating intensity-based absolute quantification (iBAQ) values reported for MYDGF to those of several eosinophil granule proteins of known abundance in a global proteomic study of eosinophils (10,12).…”
Section: Resultsmentioning
confidence: 63%
“…Our interest in MYDGF stemmed from a quantitative proteomics study in which C19orf10 was reported as the 559 th most abundant protein of human blood eosinophils, present at 1-3% of the molar abundances of the major eosinophil granule proteins RNASE2, RNASE3, PRG2, and PRG3 (10). When we realized that C19orf10 had been characterized functionally as MYDGF (9), we asked whether eosinophils represent a second myeloid source of releasable MYDGF.…”
Section: Introductionmentioning
confidence: 99%